Modulation of J774.1 Macrophage l-Arginine Metabolism by Intracellular Mycobacterium bovis BCG - Peteroy-Kelly, Marcy A. (American Society for Microbiology, 2003)
Using a Mycobacterium bovis BCG mutant (AS1) lacking a Bacillus subtilis l-arginine transporter homolog, we demonstrate here that the interaction between intracellular mycobacteria and the macrophage with respect to l-arginine transport and metabolism is quite complex. Intracellular AS1 stimulates macrophage l-arginine transport and accumulates 2.5-fold more (3)H label derived from l-arginine than does the wild type. These studies suggest that the accumulation of (3)H label reflects the acquisition of metabolites of l-arginine produced by the macrophage.